Haemophilus influenzae isolated from cerebrospinal fluid - Frequency of biotypes and serotypes - Landoraf, Ilka Maria (1991)
Haemophilus influenzae are causal agents of human diseases, chiefly meningitis, all over the world. In the examinations of CSF in the laboratory of Bacteriology, Instituto Adolfo Lutz, São Paulo, SP, this bacterium was the one most frequently isolated, together with Neisseria meningitidis and Streptococcus pneumoniae. For the characterization of H. influenzae species and biotypes definition, biochemical tests were performed, as well as serotyping of the capsulated strains. From 1977 to 1990, 1.000 strains of H. influenzae isolated from CSF were studied. Among biotypes, the most frequent was I (70,9%) and the next one was II (27,5%). Concerning serotypes, “b” was the most prevalent (99,3%), but type “a” (0,6%) and “c” (0,1 %) were also found.